Citrate supplement facilitated muscle growth and renal maturation - Michiaki Abe; Kazuhiko Kawaguchi; Satomi Yamasaki; Toshiki Nakai; Masaharu Hatachi; Takanori Mizuno; Atsuko Masaura; Naonori Kumagai; Tadashi Ishii (PLoS ONE, 2026)
Citrate supplementation is well known to alleviate muscle fatigue. Furthermore, our previous clinical study revealed that citrate supplementation prevents renal oxidative stress and dysfunction. We hypothesize that an interaction between muscle and kidney tissues underlies the effects of citrate supplementation. This study investigated the effects of a citrate agent, potassium citrate/sodium citrate (PCSC), on muscle and renal functions. Male Sprague-Dawley rats were randomly assigned to two groups (control and PCSC groups). PCSC (2000 mg/kg body weight) was administered orally administrated for one week. Kidney weight, vastus lateralis muscle weight, and renal function were compared between the groups. Subsequently, the kidney and muscle tissues were analyzed using metabolomics. The PCSC group showed a significant increase in muscle mass relative to the weight gain ( p = 0.0472). Renal function development with growth was more pronounced in the PCSC group ( p < 0.0001). Metabolomic analysis of muscle tissue in the PCSC group revealed increased alanine levels and decreased levels of sarcosine, creatinine, and NADPH/NADP+ ratio. In the kidney tissue, PCSC supplementation led to elevated N,N-dimethylglycine, urea, and the ratio of malic acid to aspartate, while betaine aldehyde, carnitine, and Fisher’s ratio decreased. The study concluded that PCSC supplement facilitated muscle growth metabolically through an alanine-associated pathway and renal function development by increasing intrarenal urea and accelerating the malate-shuttle and the betaine pathway. These findings indicate PCSC’s potential impact of PCSCs on muscle-kidney interactions.